Cross-national comparison on the meaning of emoji to describe emotions elicited by foods in preadolescents. (February 2023) - Sick, J.; Almli, V.L.; Dinnella, C.; Berget, I.; Monteleone, E.; Spinelli, S.
Highlights: Italian and Norwegian children describe emoji with overlapping emotional meaning. CATA Emoji Pair Questionnaire can measure food-elicited emotions in preadolescents. Emoji pairs discriminated across and within food categories presented as food names. Emoji pairs discriminated between food names despite similar liking of the products. Results help for better understanding of preadolescents' food preferences. Abstract: Emoji are supposed to simulate facial expressions that convey specific emotions or other situational meanings that are language-independent indicators of emotions with shared meanings between different countries. However, some research demonstrated that the meaning of emoji can differ across countries in adults, but little is known about preadolescents. The aim of Study 1 was to compare the semantic emotional meaning of emoji to describe food experiences between 11 and 13-y.o. Italian (n = 92) and Norwegian (n = 109) preadolescents by asking children to describe 46 emoji with emotion words (n = 31) using the Check-All-That-Apply format. Spearman's correlation on the relative frequencies resulting from the Cochran's Q test and Multiple Factor Analysis (MFA) on the total frequencies of emotion words were applied to compare the emotional meaning between countries. Italian and Norwegian preadolescents were found to describe emoji with overlapping emotional meaning. This allowed the application of an emoji-based self-report questionnaire (CATA Emoji Pair Questionnaire) to measure food-elicited emotions in response to 28 food names of three food categories (fruits, vegetables, desserts/juices) in 148 Norwegian preadolescents (11–13-y.o.) (Study 2). Results showed that emoji pairs discriminated across and within food categories. Emoji pairs were shown to discriminate between food names in the vegetable and dessert/juice category despite similar liking of the products, and to give important additional information helping a better understanding of preadolescents' food preferences.